The Effect of The Stake Structure Models Pod Quality of Several Yardlong Bean Varietries - Dewi Sartika; Taryono Taryono; Rahmi Sri Sayekti (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2020)
Yardlong bean is one of the commodities with very high economic value. To obtain good quality pods, it requires the right cultivating techniques such as the use of stake model and the use of superior varieties. The objectives of this study were to investigate the effect of stake model and varieties on the quality of yardlong bean pods. This research was conducted on the Agrotechnology Innovation Center of Universitas Gadjah Mada at March-June 2019. This research was arranged in factorial treatment design with Randomized Complete Block Design (RCBD) using three blocks as replication. The irst factor is the stake model i.e. single, double, and triangle. The second factor is varieties included Parade Tavi, Pujangga, Katrina, Wulung, and Kaloka. The observed quantitative data were analyzed using analysis of variance (ANOVA), followed by Scott-Knott with the level of credibility at 5 %. The results showed that the use of the stake models on different varieties does not indicated a signiicant impact on the quality of produced pod.